Voltage Differencing Buffered Amplifier Realisation Using 32 nm FinFET Technology and Universal Filter Applications - Altan Yagci, Sevda; Konal, Mustafa; Kacar, Firat (Elektronika ir Elektrotechnika, 2024)
This paper presents high-frequency universal filter applications based on a voltage differential buffered amplifier (VDBA) using 32 nm fin field effect transistor (FinFET) technology. FinFET technology is a promising alternative to complementary metal-oxide-semiconductor (CMOS) technology to avoid the problems caused by the decrease in transistor size as the technology evolves. In addition to the manufacturing process being similar to CMOS technology, FinFET technology offers many advantages, such as reduced short channel effects, higher drain current, reduced static leakage current, faster switching time, lower supply voltage, lower power consumption, and higher efficiency. The VDBA active circuit block, which has high input impedance and low output impedance, is preferred for high-frequency and high-bandwidth applications. It is advantageous to design active filter circuits using VDBA because of its superior features, such as lower power consumption, higher bandwidth, wider range linearity, and the ability to implement the proposed circuits without external resistors. In this study, FinFET-based VDBA and filter application are simulated with the Spice simulation programme using 32 nm PTM technology parameters. Simulation results using 32 nm FinFET technology are compared with those using 0.18 µm TSMC technology. It is concluded that 32 nm FinFET technology reduces power consumption by 98.8 % and increases bandwidth by 145 times. The successful results show that FinFET technology is superior to CMOS technology in analogue circuit design. FinFET-based VDBA circuits and filters will be more advantageous in the design of signal processing and biomedical applications.